Collective defense treaties : with maps, texts of treaties, a chronology, status of forces agreements, and comparative chart / [Prepared by Helen Mattas]. - United States. Congress. House. Committee on Foreign Affairs. (Tufts University. Tisch Library., 2017)
1 online resource (514 pages); At head of title: 91st Congress, 1st session. Committee print.; Record is based on bibliographic data in ProQuest U.S. Congressional Research Digital Collection (last viewed May 2010). Reuse except for individual research requires license from ProQuest, LLC.; Revised compilation.; Tisch Outsourced Digitization 2017-10-02